Urine Voiding Pattern Analysis in MPTP Mouse Model of Parkinson’s Disease - Konthapakdee, Nipaporn; Sa-ih, Nusaib; Cheaha, Dania; Kumarnsit, Ekkasit (Journal of Physiological and Biomedical Sciences, 2019)
Urinary bladder dysfunction, e.g., urinary frequency, urgency, and incontinence, is one of common nonmotor symptoms of patients with Parkinson’s disease (PD). 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP) is widely used to induce Parkinson’s disease-like in animal models. However, it remains elusive whether this model reflects urinary bladder dysfunction in PD patients. This study aims to investigate the urine voiding pattern of MPTP-induced Parkinson’s disease-like in mice using spontaneous voiding spot analysis (VSA). Male ICR mice (8 weeks old) were injected with MPTP (10 mg/kg in normal saline, i.p.) once a day for 5 consecutive days, while the control group received normal saline. Voiding pattern was investigated at day 21 after the last treatment. Filter paper and metal wire mesh were placed in the cages to determine urine pattern of the animals for 4 hours with free access to food and water. Thereafter, the urine-stained filter paper was visualized under UV light and imaged. Urine spot number, urine volume, number of small and large urine spots, percentage of volume in the center and corner were quantified. MPTP-treated mice had a significant increase in total urine spot number (control, 8.20 ± 3.0, vs MPTP, 20.40 ± 3.73, P < 0.05, Student’s unpaired t-test; n = 5 in each group) and number of small spots compared to control (control, 4.60 ± 2.62 vs MPTP, 14.80 ± 3.09, P < 0.05, Student’s unpaired t-test; n = 5 each). There was no significant difference in total urine volume, number of large urine spots, and percentage volume in the center and corner of the cages. Our findings suggest that MPTP-induced Parkinsonian-like symptoms in mice could potentially be used as a model to investigate bladder dysfunction in Parkinson’s disease.